Optimization of human capital management to drive organizational performance towards business targets: case study at pt pertamina persero – mor v - Zuhroni, Mohamad; Ghazali, Achmad Fajar (The Indonesian Journal of Business Administration, 2016)
Abstract. In high business competition today, human capital is a major asset for the company to drive other assets and provide a guaranty to be able to perform on the top level in a relative long period. Nevertheless, in order to get the benefit of human capital asset, these asset need to be managed in a proper way and in line with company’s strategy. Pertamina – MOR (Marketing Operation Region) V is facing extraordinary business challenges. Carry out duties as the company's main revenue driver in decreasing oil prices recently, Pertamina MOR - V is expected to boast organizational performance and optimize all of its capitals, especially human capital. This study aims to elaborate how the implementation of human capital management, which drivers of human capital management that have significant impact on organizational performance, and determine the most appropriate intervention programs for those drivers. The research approach used in this study is a quantitative approach that starts from an online survey sent to the respondents including all employees of Pertamina - MOR V. After the survey data collected, statistical analysis applied and followed by a focused groups discussion to encounter and obtain a clear understanding of the measurement findings emerged from the data questionnaire. Keywords: human capital management, organizational performance, and organizational competitiveness.